Threat and protection status analysis of the alpine flora of the Pyrenees - García Girón, Isabel; Martínez García, Felipe (Mediterranean Botany, 2018)
Threat and protection statuses have been analyzed for the Alpine vascular flora of the Pyrenees, i.e., species that live mainly 2,300 masl (Alpine and Subnival levels). They have been cataloged as 387 different taxa (onwards: Alpine Flora Catalogue, AFC), many of them of conservationist interest, especially in the Iberian context, due to the abundance of endemisms and relict populations. This analysis presents an added difficulty derived from this territory’s administrative situation. The region extends over three countries: Spain, France and Andorra. The first two are divided into four autonomous communities and three regions, respectively. Threat and protection statuses have been assessed according to the presence of AFC species in Red Lists (Spain: RL 2010, Andorra: RL 2008 and France: RL 2012) and catalogues of protected species. In the latter case, it has been analyzed at national level (Spain: LWSSPR-SCTS and France: LPPSNT) and regional level: Spanish autonomous communities and French regions. Andorra lacks catalogue of protected flora. Results demonstrate that, of the 387 AFC species, 46 (12%) are included in some of the national red lists: 8 Spain, 30 Andorra and 13 France. None of the 8 Spanish threatened species appears in the LWSSPR, and in France only 3 of the 13 threatened are protected. In Andorra, none. With respect to threat status: 11 are CR (2 Spain + 9 Andorra +1 France); 11 EN (1 Spain + 8 Andorra + 2 France) and 27 VU (5 Spain + 13 Andorra + 10 France). At national level, there are 14 protected taxa: 3 Spain, and 13 France. Atregional level, there are 52 protected taxa in some of the lists from Spain and 47 from France, The Basque Country and Midi-Pyrenees are the AACC with more number of protected species.